Fruits basket. 1 - Takaya, Natsuki, 1973- (Fruits Basket, 2016)
"After a family tragedy turns her life upside down, plucky high schooler Tohru Honda takes matters into her own hands and moves out ... into a tent! Unfortunately for her, she pitches her new home on private land belonging to the mysterious Sohma clan, and it isn't long before the owners discover her secret. But as Tohru quickly finds out when the family offers to take her in, the Sohmas have a secret of their own--when embraced by the opposite sex, they turn into the animals of the Chinese zodiac!"--